2017
DOI: 10.1007/s10393-017-1291-4
|View full text |Cite
|
Sign up to set email alerts
|

Rodent-Borne Bartonella Infection Varies According to Host Species Within and Among Cities

Abstract: It is becoming increasingly likely that rodents will drive future disease epidemics with the continued expansion of cities worldwide. Though transmission risk is a growing concern, relatively little is known about pathogens carried by urban rats. Here, we assess whether the diversity and prevalence of Bartonella bacteria differ according to the (co)occurrence of rat hosts across New Orleans, LA (NO), where both Norway (Rattus norvegicus) and roof rats (Rattus rattus) are found, relative to New York City (NYC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 53 publications
6
45
1
Order By: Relevance
“…Our overall estimate of 38% infection prevalence in New Orleans is comparable to count-based estimates reported for other areas where A. cantonensis is considered endemic ( 19 , 20 , but see 21 ). We also found A. cantonensis in rats across New Orleans and in neighboring St. Bernard Parish, which contrasts with the patchy distributions exhibited by other rodent-associated pathogens in cities ( 22 25 ). Although rat lungworm is present across New Orleans, infection prevalence varied according to geography and rodent host species, suggesting the risk for transmission to humans might be mediated in part by geographically variable landscape features that affect commensal rats ( 13 , 14 ).…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Our overall estimate of 38% infection prevalence in New Orleans is comparable to count-based estimates reported for other areas where A. cantonensis is considered endemic ( 19 , 20 , but see 21 ). We also found A. cantonensis in rats across New Orleans and in neighboring St. Bernard Parish, which contrasts with the patchy distributions exhibited by other rodent-associated pathogens in cities ( 22 25 ). Although rat lungworm is present across New Orleans, infection prevalence varied according to geography and rodent host species, suggesting the risk for transmission to humans might be mediated in part by geographically variable landscape features that affect commensal rats ( 13 , 14 ).…”
Section: Discussioncontrasting
confidence: 91%
“…Waugh et al ( 19 ) similarly reported differences in intensity and prevalence in rats from Jamaica according to size but not sex, although an earlier study found that female Norway rats were more likely to be infected ( 26 ). Evidence that A. cantonensis infection differs by host age contrasts with findings for other urban rodent–associated pathogens, including flea-vectored Bartonella bacteria ( 25 ). The finding of distinct Bartonella species in Norway rats and roof rats ( 25 ) suggests that co-occurrence does not facilitate pathogen transmission, whereas our results indicate otherwise.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Surprisingly, no Bartonella-positive rats were found in New York City among 87 rats cultured during the survey conducted by Ellis et al (1999). In two other studies conducted in five sites within New York City, 33% (25/133) R. norvegicus were Bartonella-positive by PCR (Firth et al, 2014) and 23% (30/133) by culturing (Peterson et al, 2017). Ellis et al (1999) described seven genotypes of Bartonella among 63 isolates obtained from R. norvegicus.…”
Section: Canadamentioning
confidence: 95%
“…Interestingly, four rats from one location carried B. tribocorum, the bacterium dominant in rats in Los Angeles; whereas four Bartonella-positive rats from another location carried another bacterium, B. coopersplainsensis, originally described from Rattus leucopus in Australia (Gundi et al, 2009) and the most prevalent species in rats from New Zealand (Helan et al, 2018). In the U.S., this bacterium was found only in R. rattus from New Orleans (Peterson et al, 2017).…”
Section: United Statesmentioning
confidence: 98%